Español The conflict of feminist ideology in the Fang culture: an approach to the study of patriarchy in Equatorial Guinea - Bituga-Nchama, Pedro (2020)
This article aims to show the conflict between feminist ideology and the Fang culture of Equatorial Guinea. This study shows the reason why the roots of feminism as an ideology within the culture mentioned above are difficult. Feminism is a universal ideology that aims to end patriarchy. With this reality in mind, there is an aversion to feminism in Fang culture because it is conceived as a threat to the order established by the patriarchal system that has oppressed the Fang woman for many years. Admittedly, things are starting to change nowadays because there is an awareness of women who question everything that has been said that was normal for women. The solution proposed is that in order to avoid the submission of the Fang woman, she has to be educated in equality. The main results of this study show that feminism is necessary for the Fang woman to realize that she is also a person and deserves to be treated as such, without discrimination or stigmatization. In relation to the consequences of this solution, it should be noted that if both men and women are educated in equality, a more equitable society that does not reject feminist ideology would be buil,t because it is considered harmful to Fang women.